Operation of a Grid-Forming Converter Controlled by the Flux Vector - Juan Dolado Fernandez; Eduardo Rausell Navarro; Jose Luis Rodriguez Amenedo; Joaquin Eloy-Garcia; Santiago Arnaltes Gomez (IEEE Access)
The electric power system is undergoing a significant transition. Renewable energy generation capacity has increased, leading to the displacement of synchronous generators (SG) and a growing concern about grid stability due to the decrease of rotating inertial energy. Grid-forming (GFM) converters have become a technological solution to this challenge, as they are capable of operating in low strength system conditions and helping to stabilize the voltage and frequency of the grid. In this paper, a novel control scheme for GFM converters is validated in a commercial converter according to the National Grid ESO, called National Energy System Operator (NESO) since October 2024. The control scheme uses the flux vector as a simple and effective method for limiting the active and reactive currents without internal current loops. For this purpose, a hardware test bed has been implemented consisting of two DC sources emulating a photovoltaic (PV) plant which feed the DC bus a voltage source converter (VSC), a grid emulator which allows to generate the desired disturbances in the grid to evaluate the converter’s response and a three-phase load. The results obtained have validated that these GFM converters based on the flux vector are capable of synchronizing with the grid, responding against frequency disturbances like phase jumps or faults in the grid and operating in islanded mode. In addition, the innovative method used to limit the active and reactive current has also been tested, comparing its performance with that of a conventional GFM scheme, showing an improvement in the response stability.